KAJIAN AWAL SIMULASI BANJIR DI BENGAWAN SOLO BERBASIS DATA GSMaP DAN MODEL CUACA NUMERIK: (Studi Kasus Banjir Bengawan Solo 05 – 07 Maret 2019) - Aries Kristianto; Putri, Deffi Munadiyat (Jurnal Meteorologi Klimatologi dan Geofisika, 2019)
ABSTRACT Flood prediction and warning systems are important processes that can provide notification to relevant authorities and the general public. Floods hit a number of areas such as Madiun, Ngawi, Ponorogo and Bojonegoro and causes various losses in early March 2019. The purpose of this study is to simulate discharges during floods from 05 until 07 March 2019. IFAS as a rainfall-runoff modelling analysis using GSMaP as default data for simulation. This study uses numerical weather prediction which are, ERA-Interim and FNL data as rainfall input data. The numerical weather data model is downscaled before the simulation process is carried out. The simulation is reviewed at two discharge observation offices which are Ketonggo and Ahmad Yani. Simulation results show that the increasing in water discharge occurs when rain falls both at the observation point and in the upstream area. The time needed to reach the discharge peak in the downstream area towards the peak of the upstream rain is 6 hours. Verification of GSMaP simulation discharges and numerical weather models on observational discharge data shows that the numerical weather model is able to represent the observation discharge, especially after the raising limb process is complete. Keywords: IFAS, GSMaP, Hydrograph, FNL, ERA-Interim